2020
DOI: 10.1016/j.forc.2020.100237
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral similarity mapping applied to fentanyl analogs

Abstract: This manuscript outlines a straightforward procedure for generating a map of similarity between spectra of a set. When applied to a reference set of spectra for Type I fentanyl analogs (molecules differing from fentanyl by a single modification), the map illuminates clustering that is applicable to automated structure assignment of unidentified molecules. An open-source software implementation that generates mass spectral similarity mappings of unknowns against a library of Type I fentanyl analog spectra is av… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…This is an initial facet of identifying an unknown analyte using the instrument's library matching program which can be extremely valuable but need to be considered with caution when assigning a chemical structure to an unknown analyte. [149][150][151] Thus, subsequent analyses involving quadrupole time-of-flight high resolution mass spectrometry (QTOF-MS) couped to an ultra-high performance liquid chromatography (UHPLC) unit, nuclear magnetic resonance (NMR) and infrared spectroscopy (IR) were needed in order to fully identify acrylfentanyl as the opioid. The amount of the acrylfentanyl hydrochloride was eventually determined using high performance liquid chromatography and triple quadrupole spectrometry (LC-MS-MS).…”
Section: Acrylfentanylmentioning
confidence: 99%
“…This is an initial facet of identifying an unknown analyte using the instrument's library matching program which can be extremely valuable but need to be considered with caution when assigning a chemical structure to an unknown analyte. [149][150][151] Thus, subsequent analyses involving quadrupole time-of-flight high resolution mass spectrometry (QTOF-MS) couped to an ultra-high performance liquid chromatography (UHPLC) unit, nuclear magnetic resonance (NMR) and infrared spectroscopy (IR) were needed in order to fully identify acrylfentanyl as the opioid. The amount of the acrylfentanyl hydrochloride was eventually determined using high performance liquid chromatography and triple quadrupole spectrometry (LC-MS-MS).…”
Section: Acrylfentanylmentioning
confidence: 99%
“…Examples include Desorption ElectroSpray Ionization (DESI) [28][29][30], Paper-Spray (PS) [31][32][33], Low Temperature Plasma (LTP) ionization [34], Atmospheric Solids Analysis Probe (ASAP) [35] and Direct Analysis in Real Time (DART) [36][37][38][39][40]. When coupled with high-resolution accurate mass spectrometry and MS/MS techniques, the identification and characterization of unexpected or novel drug substances may potentially be achieved using these approaches, via assignment of the molecular formulae of the observed ions and by similarities in MS/MS fragmentation behavior compared to structurally homologous known substances within an established drug class [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of novel data analysis and interpretation, Gilbert et al demonstrated how principal component analysis can be used for the classification of fentanyl analogues based on their gas chromatography mass spectrometry (GC-MS) spectra [34]. Moorthy et al showed the ability to use GC-MS data combined with hybrid similarity searching [35] and mass spectral similarity mapping to identify previously unseen analogs [36].…”
Section: Introductionmentioning
confidence: 99%